Why gender matters : what parents and teachers need to know about the emerging science of sex differences - Sax, Leonard (New York : Harmony Books, 2017)
A revised and updated edition (with more than 70% new material) of the evergreen classic about the innate differences between boys and girls and how best to parent and teach girls and boys successfully, with completely new chapters on sexual orientation and on transgender and intersex kids.
Differences -- Smelling, seeing, and hearing -- Risk -- Aggression -- School -- Sex -- Drugs and alcohol -- Social media and video games -- Gender nonconforming -- Lesbian, gay, bisexual -- Intersex and transgender -- The male/female mistake.
Includes bibliographical references and index.
Keywords: Sex role; Sex differences; Child development; Child psychology; Child rearing; FAMILY & RELATIONSHIPS / Parenting; PSYCHOLOGY / Developmental / Child; SOCIAL SCIENCE / Gender Studies; Sex differences (Psychology.)